The SwissFEL soft X‐ray free‐electron laser beamline: Athos. (21st June 2019) - Abela, Rafael; Alarcon, Arturo; Alex, Jürgen; Arrell, Christopher; Arsov, Vladimir; Bettoni, Simona; Bopp, Markus; Bostedt, Christoph; Braun, Hans-Heinrich; Calvi, Marco; Celcer, Tine; Craievich, Paolo; et al.
Abstract : An overview is given of the SwissFEL soft X‐ray free‐electron laser (FEL) beamline, called Athos, and its numerous operation modes. In particular, several key hardware components are described, which enable these modes. The main FEL parameters and expected performance figures are also reported. Abstract : The SwissFEL soft X‐ray free‐electron laser (FEL) beamline Athos will be ready for user operation in 2021. Its design includes a novel layout of alternating magnetic chicanes and short undulator segments. Together with the APPLE X architecture of undulators, the Athos branch can be operated in different modes producing FEL beams with unique characteristics ranging from attosecond pulse length to high‐power modes. Further space has been reserved for upgrades including modulators and an external seeding laser for better timing control. All of these schemes rely on state‐of‐the‐art technologies described in this overview. The optical transport line distributing the FEL beam to the experimental stations was designed with the whole range of beam parameters in mind. Currently two experimental stations, one for condensed matter and quantum materials research and a second one for atomic, molecular and optical physics, chemical sciences and ultrafast single‐particle imaging, are being laid out such that they can profit from the unique soft X‐ray pulses produced in the Athos branch in an optimal way.